Telaah Kritis Kurikulum 1973 Kurikulum Proyek Perintis Sekolah Pembangunan (PPSP), Kurikulum 1975 (Kurikulum Sekolah Dasar) dan Kurikulum 1984 - Arry Widyanti; Andria Sari; Asih Umi Kholifah; Memik Nor Fadilah; Munirotun Munirotun; Umi Royani; Ngasbun Egar (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of curriculum in Indonesia reflects the dynamic interplay of social, political, and national education policy shifts over time. This study aims to analyze and compare the 1973 Pilot Project for the Developmental School (PPSP) Curriculum, the 1975 Curriculum, and the 1984 Curriculum, focusing on their historical background, content, implementation, evaluation, and relevance to current educational contexts. Using a descriptive-critical approach, this research is based on literature review of curriculum documents, education policies, and expert opinions. The findings reveal that each curriculum embodies distinct characteristics aligned with the national development agenda and prevailing educational paradigms of its time. The 1973 PPSP Curriculum emphasized experimental innovation in teaching and learning, the 1975 Curriculum promoted instructional objectives through structured lesson units, while the 1984 Curriculum introduced the concept of Active Student Learning (CBSA) as a core teaching method. This study concludes that a historical understanding of curriculum evolution is crucial for designing future curriculum that are contextual, adaptive, and responsive to the challenges of modern education.